The Agent Brain: A Review of Non-invasive Brain Stimulation Studies on Sensing Agency - Crivelli, Davide; Balconi, Michela (Frontiers in Behavioral Neuroscience, 2017)
According to philosophy of mind and neuroscientific models, the sense of agency can be defined as the sense that I am the one that is generating an action and causing its effects. Such ability to sense ourselves as causal agents is critical for the definition of intentional behaviour and is a primary root for human interaction skills. The present mini-review aims at discussing evidences from non-invasive brain stimulation studies targeting functional correlates of different aspects of agency and evidences on the way stimulation techniques affect such core feature of human subjective experience. Clinical and brain imaging studies helped in defining a neural network mediating agency-related processes, which includes the dorsolateral prefrontal cortex (dlPFC), the cingulate cortex (CC), the supplementary and pre-supplementary motor areas (SMA and pre-SMA), the posterior parietal cortex (PPC) and its inferior regions, and the cerebellum. However, while the plurality of those structures mirrors the complexity of the phenomenon, their actual roles with respect to different components of the experience of agency have been primarily explored via correlational techniques, without a clear evidence about their causal significance with respect to the integration of sensorimotor information, intentionalization, and action monitoring processes. Therefore, insights into the specific causal role of different cortical structures can be specified by using non-invasive brain stimulation (NIBS) techniques, in order to provide improved understanding into the bases of our ability vs. inability to properly act in complex social contexts.